DANA TALANGAN UMRAH DALAM PERSPEKTIF HUKUM ISLAM - Romli Ronan (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2018)
Umrah worship is a worship that has high urgency in the life of Muslim communities in Indonesia. In addition to having a high value of merit beside Allah SWT, umrah worship is also an opportunity for every Muslim to set foot for worship in two holy cities glorified by the Creator. The high number of devotees of worship is shown by the increasing number of umrah worshipers and umrah service bureaus from year to year. Along with this, more and more practice of bailouts in umrah worship, both through banking and non-banking bailouts. The phenomenon that is a problem is how the real concept of istitha'ah in umrah worship in Islamic teachings, and also how it reviews Islamic law on umrah worship by using bailouts. The researcher used three theories as scalpel to discuss the issue under study. The three theories in question include maslahah al-mursalah, qiyas, and fiqh rules (qawa'id al-fiqhiyyah). By using a conceptual approach and supported by secondary data, the results obtained that istitha'ah in umrah worship have similarities with istitha'ah in the pilgrimage, namely the ability of both physical and material to go to the holy land. The utilization of bailouts in umrah worship depends on the condition of the pilgrims who are reluctant, as well as the nature and form of bailouts provided. The five legal provisions apply by looking at the economic situation and the ability of someone who does an Umrah trip